Probabilistic splicing systems - Turaev, Sherzod; Selvarajoo, Mathuri; Selamat, Mohd Hasan; Sarmin, Nor Haniza; Fong, Wan Heng (Springer-Verlag Berlin Heidelberg, 2013)
In this paper we introduce splicing systems with probabilities, i.e., probabilistic splicing systems, and establish basic properties of language families generated by this type of splicing systems. We show that a simple extension of splicing systems with probabilities may increase the computational power of splicing systems with finite components.